Production of Λ+c baryons in proton-proton and lead-lead collisions at √snn = 5.02 TeV - Sirunyan, A. M. (2020)
The transverse momentum (pT) spectra of inclusively produced Λ+c baryons are measured via the exclusive decay channel Λ+c pK ¯π+ using the CMS detector at the LHC. Spectra are measured as a function of transverse momentum in proton-proton (pp) and lead-lead (PbPb) collisions at a nucleon-nucleon center-of-mass energy of 5.02 TeV. The measurement is performed within Λ+c the rapidity interval /y/ < 1 in the pT range of 5–20 GeV/c in pp and 10–20 GeV/c in PbPb collisions. The observed yields Λ+c of for pT of 10–20 GeV/c suggest a suppression in central PbPb collisions compared to collisions scaled by the number of nucleon-nucleon (NN) interactions. The Λ+c/D0 production ratio in collisions is compared to theoretical models. In PbPb collisions, this ratio is consistent with the result from collisions in their common pT range.